DEMOCRATIZING LANGUAGE PROFICIENCY: THE IMPACT OF GENERATIVE AI ON LEARNER AUTONOMY AND ACADEMIC INTEGRITY IN SECOND LANGUAGE ACQUISITION - Delsa Miranty; Hassan Ali; Nurul Huda (Yayasan Adra Karima Hubbi, 2026)
Generative artificial intelligence has rapidly transformed second language acquisition by providing learners with continuous access to automated feedback, translation support, grammar correction, and interactive language practice. Expansion of AI-assisted learning environments has increased opportunities for independent language development and reduced barriers associated with instructional access and linguistic anxiety. Simultaneous growth of AI integration in education has also generated concerns regarding academic integrity, technological dependency, and the authenticity of learner language production within academic contexts. This study aimed to examine the impact of generative AI on learner autonomy and academic integrity in second language acquisition. Particular attention was directed toward analyzing how AI-assisted language learning influences self-regulated learning behavior, writing performance, language confidence, and ethical awareness among second language learners in higher education environments. A mixed-methods sequential explanatory design was employed involving 300 undergraduate students enrolled in second language learning programs across three universities. Quantitative data were collected through learner autonomy scales, academic integrity perception questionnaires, and AI usage surveys, while qualitative findings were obtained through interviews, classroom observations, and reflective journals. Statistical analysis included ANOVA, regression analysis, and correlation testing to identify relationships between AI usage and educational outcomes. Results demonstrated that generative AI significantly improved learner autonomy, writing performance, and language confidence through personalized linguistic support and immediate feedback. High-frequency AI users, however, exhibited stronger technological dependence and lower academic integrity awareness regarding authentic language production. Findings confirm that generative AI democratizes language learning opportunities while simultaneously requiring balanced pedagogical frameworks supporting ethical engagement, authentic linguistic development, and responsible educational technology integration.